COMPREHENSIVE NURSING CARE TO THE CANCER PATIENT AND THE FAMILY - Adriana Vicenzi; Eda Schwartz; Diana Cecagno; Aline da Costa Viegas; Bianca Pozza dos Santos; Julyane Felipette Lima (Universidade Federal de Santa Maria, 2013)
http://dx.doi.org/10.5902/217976928816 Aim: to identify actions provided by the nursing team aiming a comprehensive care of cancer patients and their families. Method: this is a qualitative, descriptive and exploratory study, developed in an outpatient oncology unit of a large hospital. Study subjects were six professionals of the nursing staff. It was used a semi-structured interview for data collection. The data were analyzed and interpreted according to the thematic analysis. Results: in this study the following themes emerged: nursing guidelines for cancer patients and their families and the strategies of the nursing team aiming a comprehensive care to the patient and family. Final Thoughts: it is expected that this study contributes to the development of actions that help cancer patients and their families in coping with the disease.